Drug Pair of Astragali Radix–Ligustri Lucidi Fructus Alleviates Acute Kidney Injury in Mice Induced by Ischemia–Reperfusion Through Inhibiting Ferroptosis - Xuanhe Liu; Dan Zhang; Yuting Xie; Mengdan Wang; Xiaochun Chen; Weijie Yu; Yuming Ma; Jia Zeng; Qixuan Long; Guangrui Huang; Jie Geng; Anlong Xu (Pharmaceuticals, 2025)
Background: Acute kidney injury (AKI), characterized by high morbidity and mortality, is primarily caused by renal ischemia–reperfusion injury (RIRI). Ferroptosis plays a key role in RIRI, yet its underlying mechanisms remain unclear. The drug pair of Astragali Radix–Ligustri Lucidi Fructus (DAL) shows promise in renal diseases, but its protective effects against RIRI and associated molecular pathways via ferroptosis inhibition are unknown. This study aimed to investigate DAL’s therapeutic effects on RIRI and its mechanisms. Methods: A mouse model of bilateral renal ischemia–reperfusion was established. Renal function (serum creatinine, Scr; blood urea nitrogen, BUN), inflammatory cytokines (TNF-α, IFN-γ, IL-6), ferroptosis markers (GPX4, MDA, GSH, tissue iron), and pathological damage were evaluated. Transcriptomic sequencing and electron microscopy analyzed gene pathways and mitochondrial structure. In HK-2 cells, oxygen–glucose deprivation/reoxygenation (OGD/R) and RSL3-induced ferroptosis models were used to assess DAL-containing serum effects via cell viability, GPX4 expression, and mitochondrial morphology. LC-MS analyzed DAL’s chemical components, and network pharmacology predicted ferroptosis-related targets. Results: DAL significantly reduced Scr/BUN levels, alleviated tubular injury, fibrosis, and apoptosis, and downregulated inflammatory cytokines and damage markers. It inhibited ferroptosis by upregulating GPX4, decreasing MDA/tissue iron, and increasing GSH. Transcriptomics revealed enrichment in lipid metabolism pathways. DAL restored the mitochondrial cristae structure; DAL-containing serum improved cell viability, blocked RSL3-induced GPX4 downregulation, and mitigated mitochondrial dysfunction. Network pharmacology identified DAL’s potential active components and targets. Molecular docking validated binding affinity and interaction patterns of active components with targets. Conclusions: DAL protects against RIRI by upregulating GPX4, preserving the mitochondrial structure, and inhibiting ferroptosis, highlighting its therapeutic potential for AKI prevention and treatment.